The SAGE Handbook of Digital Society - Housley, William (London : SAGE Publications Ltd, 2023)
This SAGE Handbook brings together cutting edge social scientific research and theoretical insight into the emerging contours of digital society. Chapters explore the relationship between digitisation, social organisation and social transformation at both the macro and micro level, making this a valuable resource for postgraduate students and academics conducting research across the social sciences. The topics covered are impressively far-ranging and timely, including machine learning, social media, surveillance, misinformation, digital labour, and beyond. This innovative Handbook perfectly captures the state of the art of a field which is rapidly gaining cross-disciplinary interest and global importance, and establishes a thematic framework for future teaching and research. Part 1: Theorising Digital Societies; Part 2: Researching Digital Societies; Part 3: Sociotechnical Systems and Disruptive Technologies in Action; Part 4: Digital Society and New Social Dilemmas; Part 5: Governance and Regulation; and Part 6: Digital Futures.
Description based on XML content.
Keywords: Digital Media; Media & Society